(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The article considers the problem of ensuring the reliability and forecasting the resource of two-layer chromium-nickel rolling rolls of the LPHND-63 design, which are subject to intensive mechanical, thermal and contact-fatigue wear under modern rolling conditions. Unforeseen failures of forming tools cause significant economic losses, which makes it necessary to develop methods for reliable assessment of their actual condition and forecasting of operating time. The paper analyzes modern approaches to increasing the operational stability of rolls, which indicates the dominance of directions related to the improvement of materials, chemical composition and heat treatment technologies. At the same time, the issue of forecasting the resource taking into account the conditions and operating schemes remains insufficiently studied. Based on statistical data, forming tools operated in various combinations of finishing and roughing stands were investigated. The homogeneity of the selections and the relationships between technological and operational parameters were assessed. A significant difference in the variation of indicators depending on the scheme of application of forming tools was established. Using multiple linear regression methods, a model for predicting the total operating time was constructed, which reflects the influence of roll hardness and the number of installations in finishing and roughing stands. The obtained equation allows quantitatively assessing the change in resource by key parameters and can be used to optimize technological schemes for using LPHND-63 rolls.